5.II Industrial Crops: Beet, coffee, oil palm, cotton and rubber - Bettencourt, E.; Konopka, J.; International Plant Genetic Resources Institute (1988)
IPGRI maintains a number of databases with summary information on ex situ germplasm collections worldwide. The data include address information on organizations holding germplasm and summary information on the type of germplasm that is maintained, such as: species names, number of accessions per species, type of accessions, etc. Currently, summary information on more than 5 million accessions worldwide is available. IPGRI attempts to keep these databases up to date by continuously incorporating new information. The updating and collation of ex situ germplasm holding data is done in close collaboration with Food and Agriculture Organization of the United Nations (FAO) which provides a similar type of data as part of its World Information and Early Warning System (WIEWS) . Synchronization of common data types is achieved through bi-monthly data exchange. Updated versions of IPGRI's ex situ germplasm holdings databases are regularly uploaded to our Internet site where they are available for interactive queries.